Magnetic properties and magnetocaloric effect (MCE) in the rare-earths (RE) based RECu2Si2 (RE = Nd and Pr) compounds. (1st April 2022) - Wang, Xin; Ma, Yihui; Zhang, Zhenqian
Abstract: The rare-earths ( RE ) based materials with large magnetocaloric effect (MCE) have been recently recognized as potential candidates for practical solid-state magnetic refrigeration. In this work, the two light RE -based ternary RE Cu2 Si2 ( RE  = Nd and Pr) compounds were fabricated by arc-melting method and investigated the structural, magnetic and magnetocaloric properties. Both RE Cu2 Si2 compounds are found to crystallize in a ThCr2 Si2 -type layered crystal structure with the I 4/ mmm space group and undergo a field-induced first-ordered magnetic transition (MT) around 13.6 and 3.5 K for NdCu2 Si2 and PrCu2 Si2, respectively. Large reversible MCE has been observed in both RE Cu2 Si2 compounds, and the magnetocaloric parameters of the maximum isothermal magnetic entropy change (-Δ S M max ) and relative cooling power ( RCP ) with the magnetic field change (Δ H ) of 0–7 T are determined to be 5.9 J/kg-K and 82.6 J/kg for NdCu2 Si2 compound and to be 8.0 J/kg-K and 67.2 J/kg for PrCu2 Si2 compound, respectively. Highlights: The ternary RE Cu2 Si2 ( RE  = Nd and Pr) compounds are synthesized. Cryogenic magnetic properties in RE Cu2 Si2 were studied. The magnetocaloric parameters in RE Cu2 Si2 compounds were determined.